Evaluation of molded and printed gelma hydrogel for bioprinting - Liaw, Shannen Xueqi (2017)
Three-dimensional (3D) bioprinting is a process that permits the user to print layer-by-layer of gels according to the given computerized instructions as to build the structure up. The 3D biostructure is the precise placing of the biological materials and living cells. 3D bioprinting can also print usable biological constructs that is suitable for medical uses such as restoration of tissues and organ functions. To achieve the aim of restoring tissues and organ functions, it is important to have a good bioink. It is because the mechanical and biological properties of the bioink, that it will affect the outcome of the result of restoring tissues and organ function. Therefore, in this study we will discuss the mechanical and biological properties about three bioinks, GelMA, Alginate and Gelatin and how mechanical properties affect the biological properties.